2014
DOI: 10.1016/j.cgh.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Rational Helicobacter pylori Therapy: Evidence-Based Medicine Rather Than Medicine-Based Evidence

Abstract: Data are available such that choice of Helicobacter pylori therapy for an individual patient can be reliably predicted. Here treatment success is defined at a cure rate of 90% or greater. Treatment outcome in a population or a patient can be calculated based on the effectiveness of a regimen for infections with susceptible and with resistant strains coupled with knowledge of the prevalence of resistance (i.e., based on formal measurement, clinical experience, or both). We provide the formula for predicting out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
314
8
15

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(343 citation statements)
references
References 58 publications
6
314
8
15
Order By: Relevance
“…(25) Resistance to clarithromycin, in particular, is responsible for a decrease in the efficacy of current triple-therapy regimens. (25)(26)(27) As antibiotic resistance profiles vary across geographical regions, knowledge of local resistance patterns and treatment outcomes is important. (26,28) A recent study of H. pylori resistance profiles in Singapore found that in the time periods of 2000-2002 and 2012-2014, resistance rates to clarithromycin (7.9% to 17.1%), metronidazole (24.8% to 48.2%) and levofloxacin (5.0 to 14.7%) have increased, whereas resistance to amoxicillin (3.0% to 4.1%) and tetracycline (5.0% to 7.6%) remained low.…”
Section: Empiric First-line Treatmentmentioning
confidence: 99%
“…(25) Resistance to clarithromycin, in particular, is responsible for a decrease in the efficacy of current triple-therapy regimens. (25)(26)(27) As antibiotic resistance profiles vary across geographical regions, knowledge of local resistance patterns and treatment outcomes is important. (26,28) A recent study of H. pylori resistance profiles in Singapore found that in the time periods of 2000-2002 and 2012-2014, resistance rates to clarithromycin (7.9% to 17.1%), metronidazole (24.8% to 48.2%) and levofloxacin (5.0 to 14.7%) have increased, whereas resistance to amoxicillin (3.0% to 4.1%) and tetracycline (5.0% to 7.6%) remained low.…”
Section: Empiric First-line Treatmentmentioning
confidence: 99%
“…Second, there are few data describing the effect of metronidazole resistance in concomitant therapy. Moreover if dual-resistance to clarithromycin and metronidazole was > 15%, the eradication rate decreased [108,109] . Finally, as with sequential therapy, when first-line treatment fails no second-line treatment for concomitant therapy has been established.…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…The current guidelines recommend H. pylori culture and susceptibility testing following two unsuccessful courses of treatment (1). Nevertheless, in regions where antibiotic susceptibility testing is unavailable, epidemiological data for secondary H. pylori resistance is essential to allow for the rational use of antibiotics following several failures in treatment (2). In this manner, the treatment success of a particular antibiotic regimen can be reliably predicted based on epidemiological data, even in the absence of individualized H. pylori culture and susceptibility testing.…”
Section: Espite 30 Years Of Experience In Treatingmentioning
confidence: 99%